2017
DOI: 10.1039/c7tb00486a
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of ECM with silk and chitosan nanocomposite materials

Abstract: Extracellular matrix (ECM) is a system used to model the design of biomaterial matrices for tissue regeneration. Various biomaterial systems have been developed to mimic the composition or microstructure of the ECM. However, emulating multiple facets of the ECM in these systems remains a challenge. Here, a new strategy is reported which addresses this need by using silk fibroin and chitosan (CS) nanocomposite materials. Silk fibroin was first assembled into ECM-mimetic nanofibers in water and then blended with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…These changes suggested that further assembly occurred during the incubation procedure and freezing process at higher temperature, resulting in more nanofiber formation. Similar to acid-assisted RSF scaffold formation, the extracellular matrix-mimetic nanofibrous structure assembled in the TS scaffolds, which would provide favorable cues for cell growth and proliferation (Calle et al, 2016;Ding et al, 2017;Gu et al, 2014;Han et al, 2016). Flt-1 CGGAGAAATCTGCTC GCTATCTTGGAAGGGA CGACACG attributed to amorphous states (Bai et al, 2015;Sang et al, 2018;Wang et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…These changes suggested that further assembly occurred during the incubation procedure and freezing process at higher temperature, resulting in more nanofiber formation. Similar to acid-assisted RSF scaffold formation, the extracellular matrix-mimetic nanofibrous structure assembled in the TS scaffolds, which would provide favorable cues for cell growth and proliferation (Calle et al, 2016;Ding et al, 2017;Gu et al, 2014;Han et al, 2016). Flt-1 CGGAGAAATCTGCTC GCTATCTTGGAAGGGA CGACACG attributed to amorphous states (Bai et al, 2015;Sang et al, 2018;Wang et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Some applications include engineering the extracellular matrix (ECM), wound healing applications, cardiac tissue regeneration, bone regeneration, or liver tissue engineering. Ding et al fabricated natural scaffolds to simulate the ECM using silk fibroin and chitosan for future applications in tissue regeneration [120]. The nanostructures demonstrated an improvement of biocompatibility, cell proliferation, and neovascularization.…”
Section: Tissue Regenerationmentioning
confidence: 99%
“…CS-contained coating also promoted the differentiation of osteoprogenitor cells and bone formation 30 32 . In recent years, researchers focused more on the applications of CS and SF mixtures in biofunctional scaffolds and coatings, which showed highly acceptable biocompatibility 33 , 34 .…”
Section: Introductionmentioning
confidence: 99%